Poor control of oxidative stress index is associated with increased DNA methylation in retinopathy patients of a sample from babylonian population - Farah A. Al-Hassan; Hawraa Sabah Al-Musawi (Medical Journal of Babylon)
Abstract Background: Retinopathy is one of almost insidious advanced neuron-vascular complications of diabetes, oneof the most common complications that lead to permanent visual impairment in the middle-aged population. Objectives: The study investigated the association between poor oxidative stress index and DNA methylation. Materials and Methods: The study included 120 participants, of whom 40 were healthy, 40 patients with retinopathy, and 40 non-retinopathy diabetes patients (type 2 diabetes mellitus (T2DM)). The total antioxidant, capacity (TAC) evaluated using Cupric ion reducing antioxidant capacity method. Reactive oxygen species (ROS) was measured using Erel method. Global DNA methylation has measured employing 5 mC% estimating using MethylFlash™ Methylated DNA Quantification Kit. Results: Current investigation indicated significant (P ≤ 0.05) accrue in TAC, ROSs, and oxidative stress index (OSI) in diabetic compared with controls. In addition, a significant (P ≤ 0.05) increase of ROSs and OSI were recorded in retinopathy compared with T2DM patients was reported. The analysis of global DNA methylation revealed that diabetic patients have a significantly (P ≤ 0.05) more 5 mC% as compared with healthy subjects. Also, the present study showed a significant rise in methylation in retinopathy compared as with T2DM patients. Regarding the correlation analysis, the current study conducted significantly (P < 0.05) positive association between DNA methylation and each of the ROSs and OSI. Also, a significant positive correlation was reported between DNA methylation and ROSs and OSI in retinopathy and T2DM. Conclusion: Global DNA methylation has an increased level in patients and could be engaged with emergence and progress of retinopathy in diabetic with poor control of oxidative stress and increased ROSs.